IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DI KABUPATEN SEMARANG PADA OBYEK WISATA PALAGAN AMBARAWA - Ahmad Hanif Nur R; Dyah Lituhayu; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Semarang Regency is one area that has great potential in the tourism sector. However, the development of tourism in Semarang Regency in the last 2 years can be have not been maximized. This happened because of the Covid-19 pandemic that entered Indonesia in early 2020. As a result, the targets of the tourism development policy in Semarang Regency could not be achieved, such as not achieving an increase in the number of tourist visits and increasing regional income in the tourism sector. This research aims to determine the implementation of policies in Semarang Regency, especially at the Palagan Ambarawa tourism object during the covid-19 pandemic, as well as analyze the factors that hinder the implementation of policies during the pandemic. This research uses a qualitative descriptive approach. Data collection techniques through interviews, observation, and documentation as well as using domain and taxonomy analysis. Based on the results of the study indicate that the implementation of tourism development policies in Semarang Regency at Palagan Ambarawa has not been fully implemented successfully. When viewed from the standards and policy objectives, tourism development in Palagan Ambarawa has not been achieved optimally. Then there are also several obstacles such as a lack of manpower, a lack of budget, and the Covid-19 pandemic that hinders the implementation of policies. The recommendation in this study is that the tourism office can collaborate with private companies in Semarang Regency, in order to get budget assistance in carrying out tourism development.